2007
DOI: 10.1051/0004-6361:20066017
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the Macho content of the Galactic Halo from the EROS-2 Survey of the Magellanic Clouds

Abstract: Aims. The EROS-2 project was designed to test the hypothesis that massive compact halo objects (the so-called "machos") could be a major component of the dark matter halo of the Milky Way galaxy. To this end, EROS-2 monitored over 6.7 years 33 × 10 6 stars in the Magellanic clouds for microlensing events caused by such objects. Methods. In this work, we use only a subsample of 7 × 10 6 bright stars spread over 84 deg 2 of the LMC and 9 deg 2 of the SMC. The strategy of using only bright stars helps to discrimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
944
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 921 publications
(989 citation statements)
references
References 48 publications
35
944
2
8
Order By: Relevance
“…For masses ∼ 10 15 g, there are strong bounds from the observed intensity of the diffuse gamma ray background (Page and Hawking, 1976), limiting their contribution to the matter density to less than one part in 10 8 . For larger masses, constraints can be deduced from microlensing techniques (Alcock et al, 2000;Tisserand et al, 2007) and from spectral distortions of the cosmic microwave background (Ricotti et al, 2008) which limit the mass to below ∼ 10 3 M .…”
Section: Primordial Black Holesmentioning
confidence: 99%
“…For masses ∼ 10 15 g, there are strong bounds from the observed intensity of the diffuse gamma ray background (Page and Hawking, 1976), limiting their contribution to the matter density to less than one part in 10 8 . For larger masses, constraints can be deduced from microlensing techniques (Alcock et al, 2000;Tisserand et al, 2007) and from spectral distortions of the cosmic microwave background (Ricotti et al, 2008) which limit the mass to below ∼ 10 3 M .…”
Section: Primordial Black Holesmentioning
confidence: 99%
“…microlensing by extended clumps of stellar masses. We note that continuous observations by EROS, OGLE and other groups (Tisserand et al 2007;Wyrzykowski et al 2009) neither revealed any sign of these extended clumps in the Galactic halo, nor provided any proof of such structures inside the Galaxy. The overwhelming majority of the light curves observed for Galactic microlensing events are well described by the gravitational field of stars (and, sometimes, of planetary mass objects).…”
Section: Introductionmentioning
confidence: 62%
“…These events could lead to such observable effects as high amplifications of the lensed image flux, "occultations" and sudden jumps of the average image positions (image centroids). There exist many observational data compiled by EROS, OGLE and other groups (Tisserand et al 2007;Wyrzykowski et al 2009) hunting for microlensing events caused by Galactic objects.…”
Section: Observational Mimicry Of the Extended Mass Microlenses And Tmentioning
confidence: 99%
“…This control has been possible only toward the SMC because it is the only field where we found cataloged variable objects. Indeed the CDS and EROS cataloges (Tisserand et al 2007) contain three variable objects within our SMC-field. We were able to identify two cepheids, HV1562 (α = 13.1550 • , δ = −72.8272 • , J2000, J = 14.7, periodicity 4.3882 days) and the EROS cepheid (α = 13.2250 • , δ = −72.7951 • , J2000, J = 16.03, periodicity 2.13581 days).…”
Section: Sensitivity Of the Analysis To The Known Variable Objectsmentioning
confidence: 99%
“…Considering the results of baryonic compact massive objects searches through microlensing (Tisserand et al 2007;Wyrzykowski et al 2010;Alcock et al 2000; see also the review of Moniez 2010), these clouds should now be seriously considered as a possible major component of the Galactic hidden matter. It has been suggested that a hierarchical structure of cold H 2 could fill the Galactic thick disk or halo (De Paolis et al 1995;De Paolis et al 1998), providing a solution for the Galactic hidden matter problem.…”
Section: Introductionmentioning
confidence: 99%